Tipong pinoy : Philippine dances. (Sl : NCAA / Felta)
A television program featuring the history and development of Philippine dances as performed by thr Ramon Obusan Folklore Dance Group.
Keywords: Philippine dances; Filipino dance; Tipong pinoy